Combination of Non-Ablative Fractional Laser with Q-Switched Laser for the Treatment of Becker’s Nevus: Efficacy and Limitations - Han, Hye Sung; Hong, Jun Ki; Yoo, Kwang Ho; Seo, Seong Jun (Annals of dermatology, 2023)
Becker's nevus (BN) is a benign hamartoma that may present as a distressing cosmetic problem. The treatment of BN poses a significant challenge as current therapeutic modalities are suboptimal and have an increased risk of adverse effects, such as scarring and dyspigmentation. We present the use of non-ablative fractional laser therapy combined with Q-switched Nd:YAG laser as a possible therapeutic option for BN treatment and review relevant literature to discuss its efficacy and limitations.